Heat sink

By using a combination of aluminum oxide particles and resins with specific particle size distribution in the heat sink, the problem of poor thinning film formation in the prior art is solved, and a heat sink with high thermal conductivity and film formation is realized, which is suitable for small-scale Portable electronic devices.

CN114641858BActive Publication Date: 2024-12-13TATSUTA ELECTRICWIRE & CABLE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202080078326.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-15
Filing Date
2020-10-27
Publication Date
2024-12-13
Estimated Expiration
2040-10-27

AI Technical Summary

Technical Problem

The existing heat sinks have poor film formation or are prone to rupture during the thinning process, making it difficult to meet the high performance and thinning needs of small portable electronic devices.

Method used

Using a combination of alumina particles and resin, the alumina particles set a specific proportion and particle size range in the particle size distribution, including peak particle sizes of 30-60 μm, 2-12 μm and 0.1-1 μm, and are surface treated by silane coupling agent. , spherical particles are formed to improve thermal conductivity and film forming properties.

Benefits of technology

It has realized a thin and good film forming fin with thermal conductivity above 3.5W/mK and a heat diffusion rate of more than 1.6×10-6m2/s. It is suitable for small portable electronic devices such as smartphones.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure DEST_PATH_IMAGE002
    Figure DEST_PATH_IMAGE002
Patent Text Reader

Abstract

The present invention provides a heat sink that can obtain good film-forming properties even if it is thin. The heat sink comprises alumina particles and resin, wherein the content ratio of the alumina particles in the heat sink is 70% by volume or more, and in the particle size distribution, the alumina particles have peaks at particle sizes of 30 to 60 μm, 2 to 12 μm, and 0.1 to 1 μm, respectively. In the particle size distribution, among the alumina particles, the proportion of alumina particles with a particle size of 30 to 60 μm is 9 to 60% by volume, the proportion of alumina particles with a particle size of 2 to 12 μm is 30 to 75% by volume, and the proportion of alumina particles with a particle size of 0.1 to 1 μm is 2 to 20% by volume.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a heat sink. Background Art

[0002] In recent years, with the development of electronic technology, heat-generating components are often used in electronic devices such as power devices. When controlling electronic circuits, it is very important to dissipate the heat from these heat-generating components to cool the entire system. For example, a heat sink can be set between the heat-generating component and the heat sink fins or metal plates, and the heat sink and the heat-generating component can be tightly fitted without gaps by pressing, and the heat conductivity of the heat sink can be used to transfer the heat generated by the heat-generating component to the heat sink fins, etc., so as to dissipate heat from the entire system.

[0003] The heat sink is made of, for example, thermally conductive inorganic fillers and resins. Inexpensive aluminum hydroxide and aluminum oxide (alumina), silicon carbide, boron nitride, and aluminum nitride with higher thermal conductivity are used as inorganic fillers. For example, acrylic resins and polyurethane resins are used as resins.

[0004] As the heat sink, for example, those disclosed in Patent Documents 1 to 3 are known.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent document 1: Japanese Patent Application Laid-Open No. 2007-277405;

[0008] Patent document 2: Japanese Patent Application Laid-Open No. 2007-277406;

[0009] Patent document 3: Japanese Patent Application Laid-Open No. 2009-274929. Summary of the invention

[0010] Technical problem to be solved by the invention

[0011] In recent years, small portable electronic devices such as smartphones have become increasingly high-performance, and with this high performance, the heat generated by the components in the portable electronic devices has also become very high. Therefore, there is a demand for heat sinks that can be used in small electronic devices such as portable electronic devices.

[0012] In addition, there is a demand for further thinning of the above-mentioned portable electronic devices, and with this demand, there is also a demand for thinner heat sinks. However, when attempting to thin the heat sinks disclosed in Patent Documents 1 to 3, problems such as poor film forming properties and failure to obtain a heat sink in the form of a sheet or the heat sink being relatively brittle and easily broken occurred.

[0013] In view of the above circumstances, an object of the present invention is to provide a heat sink sheet that can achieve good film-forming properties even if it is thin.

[0014] Technical means to solve technical problems

[0015] The inventors of the present invention have conducted intensive research to achieve the above-mentioned purpose and have found that a thin heat sink with good film-forming properties can be obtained by using resin and alumina as components constituting a heat sink, wherein the alumina has peaks in three specific particle size ranges in particle size distribution and the alumina in the three specific particle size ranges has specific ratios. The present invention was completed based on the above-mentioned findings.

[0016] That is, the present invention provides a heat sink comprising alumina particles and a resin, wherein the content of the alumina particles in the heat sink is 70% by volume or more, and in a particle size distribution, the alumina particles have peaks at particle sizes of 30 to 60 μm, 2 to 12 μm, and 0.1 to 1 μm, respectively. In the particle size distribution, among the alumina particles, the proportion of alumina particles with a particle size of 30 to 60 μm is 9 to 60% by volume, the proportion of alumina particles with a particle size of 2 to 12 μm is 30 to 90% by volume, and the proportion of alumina particles with a particle size of 0.1 to 1 μm is 1 to 20% by volume.

[0017] Preferably, in the particle size distribution, the alumina particles having a peak at 30 to 60 μm, the alumina particles having a peak at 2 to 12 μm, and the alumina particles having a peak at 0.1 to 1 μm are spherical particles.

[0018] Preferably, the heat dissipation fin has a thermal conductivity of 3.5 W / mK or more and less than 5.0 W / mK.

[0019] Preferably, the thermal diffusivity of the heat sink is greater than 1.6×10 -6 m 2 / s.

[0020] Preferably, the heat sink has a thickness of 2.3 mm or less.

[0021] Effects of the Invention

[0022] The heat sink of the present invention can obtain good film-forming properties not only for thick heat sinks but also for thin heat sinks. Therefore, the heat sink of the present invention can be preferably used in small portable electronic devices such as smart phones. DETAILED DESCRIPTION

[0023] The heat sink of the present invention contains at least alumina particles and resin. In the particle size distribution, the alumina particles contain peaks at particle sizes of 30 to 60 μm, 2 to 12 μm, and 0.1 to 1 μm, respectively. In addition, in this specification, alumina particles with a particle size of 30 to 60 μm in the particle size distribution are sometimes referred to as "first alumina particles", alumina particles with a particle size of 2 to 12 μm are referred to as "second alumina particles", and alumina particles with a particle size of 0.1 to 1 μm are referred to as "third alumina particles".

[0024] The first alumina particle is the largest among the first to third alumina particles, is a large-size particle, and mainly exerts thermal conductivity. The peak particle size of the first alumina particle is in the range of 30 to 60 μm, preferably in the range of 40 to 50 μm, and more preferably in the range of 42 to 48 μm. By using alumina particles of the above particle size as large-size particles, it is difficult for alumina particles to fall off and the heat sink to break when a thin heat sink is manufactured.

[0025] The first alumina particles are preferably spherical particles. When the first alumina particles are spherical particles, the first alumina particles have good dispersibility in the resin (especially silicone resin) as the base of the heat sink, and the film forming property is more excellent even when a thin heat sink is produced. In addition, in this specification, spherical particles refer to particles whose average roundness (circumference of an equivalent circle / circumference of a particle projection image) is greater than 0.8.

[0026] The first alumina particles are preferably surface treated with a silane coupling agent. When the surface is treated with a silane coupling agent, the first alumina particles have good dispersibility in a resin (especially a silicone resin) as a base of a heat sink, and film forming properties are more excellent even when a thin heat sink is produced. The above-mentioned silane coupling agent may be used alone or in combination of two or more.

[0027] Examples of the silane coupling agent include β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropylmethyldiethoxysilane, etc., which contain functional groups other than alkoxy groups (functional group-containing silane coupling agents); n-decyltrimethoxysilane, etc., which do not contain functional groups other than alkoxy groups (functional group-free silane coupling agents). Among them, from the perspective of good wettability with alumina particles and improved overall strength and flexibility of the heat sink, a functional group-free silane coupling agent is preferred, and a silane coupling agent with an alkyl group at the end other than alkoxy groups (alkyl group-containing silane coupling agents at the end) is more preferred, and n-decyltrimethoxysilane is particularly preferred.

[0028] The content ratio of the first alumina particles contained in the heat sink of the present invention is 9 to 60 volume % relative to the total volume 100 volume % of the alumina particles, preferably 25 to 55 volume %, more preferably 35 to 55 volume %, and further preferably 45 to 55 volume %. When the content ratio is 9 volume % or more, the thermal conductivity is excellent. When the content ratio is 60 volume % or less, when a thin heat sink is manufactured, it is difficult for the alumina particles to fall off and the heat sink to break.

[0029] The second alumina particles are the second largest particles among the first to third alumina particles, and are medium-sized particles. They are filled between the first alumina particles in the heat sink to improve the thermal conductivity between the first alumina particles. The peak particle size of the second alumina particles is in the range of 2 to 12 μm, preferably in the range of 3 to 8 μm. By using alumina particles of the above particle size as medium-sized particles, the void filling rate between the large-sized particles is high, and the thermal conductivity is excellent.

[0030] The second alumina particles are preferably spherical particles. When the second alumina particles are spherical particles, the second alumina particles have good dispersibility in the resin (especially silicone resin) that is the matrix of the heat sink, and the film-forming property is more excellent even when a thin heat sink is produced.

[0031] The second alumina particles are preferably surface treated with a silane coupling agent. When the second alumina particles are surface treated with a silane coupling agent, the second alumina particles have good dispersibility in a resin (especially a silicone resin) as a base of a heat sink, and film forming properties are more excellent even when a thin heat sink is produced. The above-mentioned silane coupling agent may be used alone or in combination of two or more.

[0032] As the silane coupling agent, the silane coupling agents that can be used for the surface treatment of the first alumina resin as exemplified and described above can be cited. Among them, from the viewpoint of good wettability with alumina particles and improved overall strength and flexibility of the heat sink, a silane coupling agent without a functional group is preferred, and a silane coupling agent having an alkyl group at the end other than an alkoxy group (a silane coupling agent containing an alkyl group at the end) is more preferred, and n-decyltrimethoxysilane is particularly preferred. n-decyltrimethoxysilane is preferred.

[0033] The content ratio of the second alumina particles contained in the heat sink of the present invention is 30 to 90 volume %, preferably 35 to 75 volume %, more preferably 40 to 60 volume %, and further preferably 40 to 55 volume % relative to 100 volume % of the total amount of the alumina particles. The second alumina particles have the above content ratio, so that the gap filling rate between the large-diameter particles is high, and the thermal conductivity is excellent.

[0034] The third alumina particle is the smallest particle among the first to third alumina particles, and is a small-diameter particle. It is filled between the first and second alumina particles in the heat sink to increase the filling rate of the alumina particles in the heat sink, thereby improving thermal conductivity. The peak particle size of the third alumina particle is in the range of 0.1 to 1 μm, preferably in the range of 0.1 to 0.5 μm, and more preferably in the range of 0.1 to 0.4 μm. By using alumina particles of the above particle size as small-diameter particles, the gap filling rate between large-diameter and medium-diameter particles is high, and thermal conductivity is excellent.

[0035] The third alumina particles are preferably spherical particles. When the third alumina particles are spherical particles, the third alumina particles have good dispersibility in the resin (especially silicone resin) as the matrix of the heat sink, and the film forming property is more excellent even when a thin heat sink is produced.

[0036] The third alumina particles are preferably surface treated with a silane coupling agent. When the third alumina particles are surface treated with a silane coupling agent, the third alumina particles have good dispersibility in a resin (especially a silicone resin) as a base of a heat sink, and film forming properties are more excellent even when a thin heat sink is produced. The above-mentioned silane coupling agent may be used alone or in combination of two or more.

[0037] As the silane coupling agent, the silane coupling agents that can be used for the surface treatment of the first alumina resin as exemplified and described above can be cited. Among them, from the viewpoint of good wettability with alumina particles and improved overall strength and flexibility of the heat sink, a silane coupling agent without a functional group is preferred, a silane coupling agent having an alkyl group at the end other than an alkoxy group (a terminal alkyl-containing silane coupling agent) is more preferred, and n-decyltrimethoxysilane is particularly preferred.

[0038] The content of the third alumina particles in the heat sink of the present invention is 1 to 20% by volume, preferably 2 to 10% by volume, more preferably 3 to 8% by volume, and even more preferably 4 to 6% by volume, relative to 100% by volume of the total amount of the alumina particles. The above content is 1% by volume or more, so that the filling rate of the alumina particles in the heat sink is high and the thermal conductivity is excellent. If the above content exceeds 20% by volume, the surface of the heat sink may be powdered, or after the heat sink is manufactured in a form sandwiched by two release sheets, the heat sink may be broken when the release sheets are peeled off.

[0039] In the heat sink of the present invention, the content ratio (total amount) of the aluminum oxide particles is 70 volume % or more, preferably 75 volume % or more, relative to 100 volume % of the heat sink of the present invention. The above content ratio is 70 volume % or more, so that the filling rate of the aluminum oxide particles in the heat sink is high and the thermal conductivity is excellent. The above content ratio is preferably 90 volume % or less, more preferably 85 volume % or less, and further preferably 80 volume % or less. If the above content ratio is 90 volume % or less, the heat sink is unlikely to become brittle, and the film forming property is excellent when a thin heat sink is made.

[0040] The resin is a component that forms the matrix of the heat sink. Examples of the resin include thermosetting resins, thermoplastic resins, and active energy ray-curable resins. The thermoplastic resins are not particularly limited, and examples include styrene resins, vinyl acetate resins, polyester resins, polyethylene resins, polypropylene resins, imide resins, and acrylic resins. The thermosetting resins are not particularly limited, and examples include silicone resins, phenol resins, epoxy resins, polyurethane resins, melamine resins, and alkyd resins. The active energy ray-curable resins are not particularly limited, and for example, polymers of polymerizable compounds having at least two (meth)acryloyloxy groups in the molecule can be used. The resins may be used alone or in combination of two or more. In addition, the thermosetting resin is a concept that includes two types of resins: resins that can be cured by heating and resins that have been cured by heating.

[0041] Among the above-mentioned resins, silicone resin is preferred from the perspective of excellent thermal conductivity. In addition, when silicone resin is used as the base resin, film-forming property is excellent even when a thin heat sink is produced. As the above-mentioned silicone resin, well-known or even commonly used silicone resins for heat sinks can be used. From the perspective of being able to well disperse aluminum oxide particles without using a solvent, a two-component curing silicone resin is preferred as the above-mentioned silicone resin. The above-mentioned silicone resin may be used alone or in combination of two or more.

[0042] The content of the above resin is not particularly limited, and is preferably 10% by volume or more, more preferably 15% by volume or more, and further preferably 20% by volume or more relative to 100% by volume of the heat sink of the present invention. If the above content is 10% by volume or more, the heat sink is unlikely to become brittle, and the film-forming property is excellent when a thin heat sink is made. The above content is preferably 30% by volume or less, and more preferably 25% by volume or less. If the above content is 30% by volume or less, the filling rate of the alumina particles in the heat sink can be increased, and the thermal conductivity is more excellent. It is particularly preferred that the content of the silicone resin is within the above range.

[0043] The thickness of the heat sink of the present invention is, for example, 0.2 to 10 mm, preferably 0.3 to 5 mm. In addition, in order to make the heat sink of the present invention thin and have good film-forming properties, so that it can be suitable for use in small portable electronic devices, the thickness is preferably 2.3 mm or less, more preferably 2 mm or less, further preferably 1.2 mm or less, further preferably 1 mm or less, and particularly preferably 0.5 mm or less.

[0044] The heat conductivity of the heat sink of the present invention is preferably 3.5 W / mK or more, and more preferably 3.6 W / mK or more. When the thermal conductivity is 3.5 W / mK or more, the heat dissipation is more excellent. For example, the thermal conductivity is lower than 5.0 W / mK.

[0045] The thermal diffusivity of the heat sink of the present invention is preferably greater than 1.6×10 -6 m 2 / s, more preferably 1.65×10 -6 m 2 / s or more, more preferably 1.7×10 -6 m 2 / s or more. If the thermal diffusivity exceeds 1.6×10 -6 m 2 / s, the heat dissipation is better.

[0046] The heat sink of the present invention may be in a form without a substrate (substrate layer), that is, a so-called "substrate-free" form, or may be a heat sink provided on at least one side of a substrate. In particular, the heat sink of the present invention can be manufactured with good film-forming properties, so that even if the heat sink is very thin, it can be obtained in a form without a substrate. In addition, the above-mentioned "substrate (substrate layer)" does not include a peeling sheet that will be peeled off when the heat sink is used.

[0047] The film forming method of the heat sink of the present invention is not particularly limited, and a well-known or even customary film forming method and molded body forming method can be adopted. Among them, roll-to-roll film forming is preferred from the perspective of continuous film forming and excellent productivity.

[0048] For example, the resin composition containing the above resin and the above aluminum oxide particles can be applied to a substrate or a release-treated surface of a release sheet to form a resin composition layer, and then cured by heating to form a film, thereby manufacturing the heat sink of the present invention. Heating can also be performed in a state where the release-treated surface of the release sheet is further attached to the above resin composition layer.

[0049] The resin composition comprises the resin and the alumina particles. The three types of alumina particles may be mixed in advance and then mixed with the resin, or the three types of alumina particles and the resin may be mixed simultaneously. The resin composition is preferably in a paste form without an organic solvent.

[0050] The method for preparing the sheet of the resin composition is not particularly limited, and a known coating method such as a sandwich method in which the material is placed between separators coated with a release agent and laminated using a laminator, a hot press molding machine, an extruder, etc. can be used.

[0051] The heat sink of the present invention combines three specific aluminum oxide particles, namely, first aluminum oxide particles having a peak at a particle size of 30 to 60 μm, second aluminum oxide particles having a peak at a particle size of 2 to 12 μm, and third aluminum oxide particles having a peak at a particle size of 0.1 to 1 μm, in specific content ratios, and mixes them with the above-mentioned resin matrix at a ratio of more than 70 volume %, so that the filling rate of the aluminum oxide particles is high and has excellent thermal conductivity, and can be obtained with excellent film-forming properties, especially excellent film-forming properties can be obtained even with a very thin thickness. Example

[0052] The present invention will be described in more detail below based on examples, but the present invention is not limited to the following examples.

[0053] Example 1

[0054] An alumina particle composition 1 was prepared by mixing 55% by volume of spherical alumina particles with a peak particle size of 45 μm, 40% by volume of spherical alumina particles with a peak particle size of 5 μm, and 5% by volume of spherical alumina particles with a peak particle size of 0.2 μm. In addition, 1 part by mass of a silane coupling agent (trade name "Z-6210", manufactured by Dow Corning Toray Industries, Ltd., n-decyltrimethoxysilane) was stirred and mixed in a solvent with respect to 100 parts by mass of the alumina particles in advance, thereby surface-treating the above three types of alumina particles with the silane coupling agent. In order to make the above alumina particle composition 1 77% by volume (the total filling amount of alumina particles is 77% by volume), a mixture of 1 part and 2 parts of a silicone resin (trade name "TSE-3062", manufactured by Momentive) was mixed to prepare a resin paste. Next, the resin paste was placed between the release-treated surfaces of the two release sheets, and laminated using a laminator to produce a laminate of [release sheet / resin paste layer / release sheet]. Subsequently, the laminate was heated at 70°C for 30 minutes to thermally cure the resin paste layer to produce the heat sink of Example 1, which was a laminate of [release sheet / heat sink / release sheet]. In Example 1, three types of heat sinks were produced, with a thickness of 0.36 mm (Type 1), a thickness of 0.73 mm (Type 2), and a thickness of 1.99 mm (Type 3).

[0055] Example 2

[0056] Alumina particle composition 2 was prepared by mixing 40% by volume of spherical alumina particles having a peak particle size of 45 μm, 50% by volume of spherical alumina particles having a peak particle size of 5 μm, and 10% by volume of spherical alumina particles having a peak particle size of 0.2 μm. In addition, the surface of the above three types of alumina particles was previously treated with a silane coupling agent as in Example 1. Subsequently, a heat sink of Example 2 was prepared in the same manner as in Example 1 except that the alumina particle composition 2 was used instead of the alumina particle composition 1. In addition, in Example 2, three types of heat sinks with a thickness of 0.45 mm (type 1), a thickness of 0.77 mm (type 2), and a thickness of 1.97 mm (type 3) were prepared.

[0057] Comparative Example 1

[0058] Alumina particle composition 3 was prepared by mixing 70 volume % of spherical alumina particles with a peak particle size of 70 μm, 12 volume % of non-spherical alumina particles with a peak particle size of 9 μm, and 18 volume % of non-spherical alumina particles with a peak particle size of 3 μm. In addition, the surface of the above three types of alumina particles was previously treated with a silane coupling agent as in Example 1. Subsequently, a heat sink of Comparative Example 1 was prepared in the same manner as in Example 1 except that the alumina particle composition 3 was used instead of the alumina particle composition 1. In Comparative Example 1, two types of heat sinks with a thickness of 0.99 mm (type 1) and a thickness of 2.32 mm (type 2) were prepared.

[0059] Comparative Example 2

[0060] Alumina particle composition 4 was prepared by mixing 80% by volume of spherical alumina particles having a peak particle size of 90 μm, 10% by volume of spherical alumina particles having a peak particle size of 5 μm, and 10% by volume of non-spherical alumina particles having a peak particle size of 3 μm. In addition, the surface of the above three types of alumina particles was previously treated with a silane coupling agent as in Example 1. Subsequently, a heat sink of Comparative Example 2 was prepared in the same manner as in Example 1 except that the alumina particle composition 4 was used instead of the alumina particle composition 1. In addition, in Comparative Example 2, two types of heat sinks with a thickness of 1.77 mm (type 1) and a thickness of 2.50 mm (type 2) were prepared.

[0061] (evaluate)

[0062] The heat sinks obtained by the examples and comparative examples were evaluated as follows. The evaluation results are recorded in the table. In addition, in all the examples, among all the alumina particles, according to the particle size distribution, the proportion of alumina particles with a particle size of 30 to 60 μm was in the range of 9 to 60 volume %, the proportion of alumina particles with a particle size of 2 to 12 μm was in the range of 30 to 90 volume %, and the proportion of alumina particles with a particle size of 0.1 to 1 μm was in the range of 1 to 20 volume %.

[0063] (1) Appearance

[0064] The appearance of the heat sink after peeling off one release sheet from the [release sheet / heat sink sheet / release sheet] laminated body obtained in Examples and Comparative Examples was evaluated according to the following criteria.

[0065] ○ (good): There was no falling off, cracking, or adhesion of the aluminum oxide particles to the peeled release sheet.

[0066] × (bad): Alumina particles fell off, cracked, or adhered to the peeled release sheet.

[0067] (2) Thermal diffusivity

[0068] The heat sinks obtained in Examples and Comparative Examples were laminated to produce a block having a thickness of 1 mm or more, and the block was measured by a laser pulse method using a thermophysical property measuring apparatus (trade name "LFA-502, manufactured by Kyoto Electronics Industry Co., Ltd.").

[0069] (3) Thermal conductivity

[0070] For each heat sink obtained in the examples and comparative examples, the specific heat at 25°C was measured by the DSC method using a differential scanning calorimeter (trade name "X-DSC7000", manufactured by Hitachi High-Tech Sciences, Ltd.). In addition, for each heat sink, the specific gravity was measured by the water displacement method using an electronic densitometer (trade name "EW-300SG", manufactured by Alfa Mirachi Co., Ltd.). Then, the thermal conductivity was calculated by calculation using the thermal diffusivity, specific heat, and specific gravity obtained above.

[0071]

[0072] The heat sink (Example) of the present invention can be manufactured with good film forming properties even if the thickness is less than 0.5 mm. In addition, the thermal diffusivity and thermal conductivity are high and the heat dissipation performance is excellent. On the other hand, in Comparative Examples 1 and 2, heat sinks with good film forming properties and a thickness of less than 2 mm were not obtained.

Claims

1. A heat sink comprising aluminum oxide particles and silicone resin, characterized in that: In the heat sink, the content of the aluminum oxide particles is 70 volume % or more; In the particle size distribution, the aluminum oxide particles have peaks at particle sizes of 30 to 60 μm, 2 to 12 μm, and 0.1 to 1 μm, respectively; In the particle size distribution, among the alumina particles, the proportion of alumina particles with a particle size of 30 to 60 μm is 9 to 60 volume %, the proportion of alumina particles with a particle size of 2 to 12 μm is 35 to 90 volume %, and the proportion of alumina particles with a particle size of 0.1 to 1 μm is 1 to 20 volume %.

2. The heat sink according to claim 1, characterized in that: In the particle size distribution, alumina particles having a peak at 30 to 60 μm, alumina particles having a peak at 2 to 12 μm, and alumina particles having a peak at 0.1 to 1 μm are spherical particles.

3. The heat sink according to claim 1, characterized in that: The heat conductivity of the heat sink is greater than 3.5 W / mK and less than 5.0 W / mK.

4. The heat sink according to claim 1, characterized in that: The thermal diffusivity of the heat sink exceeds 1.6×10 -6 m 2 / s.

5. The heat sink according to any one of claims 1 to 4, characterized in that: The thickness of the heat sink is less than 2.3 mm.